The ugly duckling and other stories - Moo-Young, Ian; Andersen, Hans Christian; Grimm, Brothers ([S. l.] : Moo Movies [production company] ; [S .l.] : Longman ELT Video [distributor], 1982)
This fairy tales contains three stories for young learners of English
This videocassette features the three titles: The ugly duckling, the emperor's new clothes, Rapunzel
Editor, Tony Fish, Peter Hearn
Storytellers: John Newton, Anne Rosenfeld
Keywords: Fairy tales; Children's stories, English; Fairy tales -- Film and video adaptations